Analisis Rasio Keuangan Dalam Mengukur Kinerja Keuangan Pada PT. Garuda Food Putra Putri Jaya Tbk Tahun 2022-2023 - Dikha Mahmudi; Dila Puspitaningsih; Diva Hayu Regita; M. Thoha Ainun Najib (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
This research aims to analyze financial ratios starting from liquidity ratios, solvency ratios, activity ratios and profitability ratios to measure financial performance at PT. Garuda Food Putra Putri Jaya Tbk. This research uses quantitative descriptive methods and the data used in this research is secondary data from PT's financial reports. Garuda Food Putra Putri Jaya Tbk in the period 2022 to 2023. The results of this research state that the financial performance of PT. Garuda Food Putra Putri Jaya Tbk in 2022-2023, if seen from the liquidity analysis, even though inventory management is very good, liquidity problems can affect the business's ability to meet short-term financial obligations, while the solvency ratio is still said to be not good because it has the value of assets financed by debt is quite high. in the activity ratio there are obstacles in optimizing asset use, which may reduce operational efficiency, even though working capital investment management is effective. If the company's profitability ratio is able to generate healthy profits from sales, increasing optimal profitability requires improvements in cost management, operational efficiency and use of capital.